The smart city and the containment of informality: The case of Dubai. (February 2021) - Breslow, Harris
I argue that Dubai's smart city project, 'Smart Dubai', is a response to the following priorities: (i) the furtherance of the city's scale-making project and worlding strategies, through the propagation of the smart city imaginary and the buildout of a smart city infrastructure modelled after those in the global north and west and used to compete for members of the creative class and other high-value residents; (ii) a project to enlarge the scope of Dubai's economy of flow. Dubai in particular, and the UAE in general, have long articulated a political economic project based on the creation of a political economy that positions the country as a regional hub within the global political economy of flow; and (iii) the containment of urban informality, which in Dubai is understood as both a disciplinary problem and an existential challenge to what is still, at heart, a rentier economy.